Degradation Characteristics of Coal Samples Under the Dry–Wet Cycle Action of Acidic, High-Salinity Solutions: Experimental Study and Fractal Analysis - Leiming Zhang; Min Wang; Bin Zhang; Xun Xi; Ying Zhang; Jiliang Pan (Fractal and Fractional)
Uniaxial compression tests were conducted on coal samples subjected to different dry–wet cycling treatments to investigate the damage and degradation mechanisms of coal samples under the dry–wet cyclic action of acidic, high-salinity solutions. The damage process of the coal samples was monitored in situ using acoustic emission (AE). The degradation evolution of the mechanical parameters and macroscopic failure modes with the number of cycles was analyzed. Based on the AE ringing parameters, the RA-AF distribution and the AE fractal dimension’s variation characteristics were studied. Additionally, scanning electron microscopy (SEM) was used to observe the microstructure of the coal samples. The results showed that with the increase in the number of dry–wet cycles, both the peak strength and elastic modulus of the coal samples exhibited varying degrees of degradation, and the failure mode gradually shifted from tensile failure to shear failure. AE ringing counts decreased progressively, while the proportion of shear cracks based on the RA-AF classification increased. At the same time, the mean AE fractal dimension of the coal samples increased, and the fractal dimension decreased with an increase in AE ringing counts. The sharp drop in fractal dimensions could serve as an early warning signal for a major failure in the coal samples. Furthermore, under the influence of dry–wet cycling in acidic, high-salinity solutions, defects such as pores and cracks in the microstructure of the coal samples became more pronounced, and the degradation effect continuously intensified.